A conjugated microporous polymer coated nano-silica microsphere and its preparation and application
By coating the conjugated microporous polymer on the surface of the amino-functionalized monodisperse nanosolid silica microspheres to form a composite nanostructure, the problem of poor dispersion after synthesis of conjugated microporous polymer is solved, and its good dispersion and fluorescence detection performance in aqueous solution is achieved, and it is used for qualitative and quantitative detection of Fe3+ and Cr3+.
Patent Information
- Application Number
- CN202111188354.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-12
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-10-12
AI Technical Summary
Conjugated microporous polymers often exist as amorphous solid powder after synthesis, which has poor dispersion, which makes it difficult to process and integrate in subsequent applications, limiting its practical application.
Amino-functionalized monodispersed nanosolid silica microspheres are used as substrates to coat conjugated microporous polymers on their surfaces through ammonia aldol condensation reaction to form a composite nanostructure, which improves dispersion and fluorescence detection performance.
The good dispersion and fluorescence detection performance of conjugated microporous polymers in aqueous solution are achieved, and the qualitative and quantitative detection of Fe3+ and Cr3+ can be detected, solving the problem of poor dispersion in traditional methods.
Smart Images

Figure CN115957704B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method of a monodisperse nano solid silica microsphere material coated with a conjugated microporous polymer and its application in qualitative and quantitative fluorescence detection of Fe in aqueous solution. 3+ or Cr 3+ Specifically, amino-functionalized monodisperse nano-solid silica microspheres, isophthalaldehyde / terephthalaldehyde / 4,4'-biphenyldicarboxaldehyde and 1,5,9-triaminotriphenylene are used as raw materials, and a layer of conjugated microporous polymer is coated on the surface of the silica microspheres by an ammonia-aldehyde condensation reaction under acid catalysis. Background Art
[0002] Conjugated microporous polymers are an emerging type of porous organic polymers, usually formed by covalent polymerization of light elements to form an amorphous powder product. By selecting different functional monomers or post-modification, the pore size, pore volume, pore surface chemical environment and functionality of conjugated microporous polymers can be precisely controlled (Reference 1. Andrew I. Cooper, et.al "Advances in Conjugated Microporous Polymers" CHEMICAL REVIEWS, 2020, 120, 2171-2214). Conjugated microporous polymers have the characteristics of π-conjugated skeleton structure, permanent pores and high specific surface area, so they are widely used in gas storage and separation, drug encapsulation, photocatalysis, chemical sensing, energy storage, biological separation, fluorescence analysis and other fields. At present, the common reaction methods for synthesizing conjugated microporous polymers include Sonogashira coupling reaction, Suzuki-Miyaura coupling reaction, Yamamoto coupling reaction and ammaldehyde condensation reaction (Document 2. Donglin Jiang, et.al "Conjugated microporous polymers: design, synthesis and application" Chemical Society Reviews, 2013, 42, 7965-8178). Among these reaction methods, the ammaldehyde condensation reaction has the advantage of not using metal catalysts, which can significantly reduce costs and avoid the impact of residual metal catalysts on subsequent applications. However, conjugated microporous polymers often exist as amorphous solid powders and have poor dispersibility, which makes it difficult to process and integrate subsequent application devices, becoming a bottleneck restricting their practical application. Iron is an element that is widely present in organisms and nature. When iron ions are overloaded in organisms, it will cause peroxidative damage in the organism (Document 3. Chen Yang, "Highly selective fluorescence detection of iron ions by rhodamine B-zirconium-based metal-organic framework composites" Analytical Chemistry, 2021, 49, 642-651). Chromium ions and their compounds are widely used in industrial production activities such as metallurgy, leather, and electroplating. With the discharge of wastewater and exhaust gas into nature, and with the gradual accumulation of the food chain, chromium ions in the human body will exceed the standard, increasing the risk of cancer (Reference 4. Anbazhagan Veerappan, et.al "Fluorescence cadmium sulfide nanosensor for selective recognition of chromium ions inaqueous solution at wide pH range" Sensors and Actuators B: Chemical, 2015, 221, 1055-1061).Therefore, it is necessary to conduct qualitative and quantitative monitoring of iron ions and chromium ions to ensure the healthy development of people's life and production activities. At present, the common methods for detecting metal ions are ultraviolet-visible spectrophotometry, atomic absorption, atomic emission, electrochemical method and fluorescence detection. Among them, the fluorescence detection method uses the change of the fluorescence signal after the fluorescent molecule combines with the object to be detected. It has the characteristics of sensitivity, selectivity, accuracy and economy. In particular, it will not cause irreversible damage to the sample to be detected. Therefore, it has been widely concerned and explored by researchers (Reference 5. Wei Kai, "Research Progress in Detection of Metal Ions in the Environment by Organic Fluorescent Molecules", Journal of Science, 2021, 66, 1614-1627).
[0003] Compared with traditional fluorescent materials, conjugated microporous polymers have open channels, which produce more chemical reaction sites, allowing more chemical substances to be detected to act, and improving detection sensitivity. Currently, the common methods for dispersing conjugated microporous polymers are grinding and ultrasonic grinding, but the dispersion of the two methods is not particularly good, and the advantages of conjugated microporous polymers have not been further brought into play (Reference 6. Jian Ding Qiu, et.al "Covalent Organic Framework Nanosheets for Fluorescence Sensing via Metal Coordination" ACS Applied Nano Materials, 2019, 2, 5342-5349).
[0004] Nano-solid silica microspheres have good monodispersity and mechanical strength. They are simple to prepare and easy to modify on the surface. They can be used as a conjugated microporous polymer loading matrix to improve the dispersibility of the conjugated microporous polymer in aqueous solution, providing convenience and repeatability for subsequent further fluorescence applications. The present invention uses amino-functionalized monodisperse nano-solid silica microspheres as a matrix, isophthalaldehyde / terephthalaldehyde / 4,4'-biphenyldicarboxaldehyde and 1,5,9-triaminotriphenylene as functional monomers, and uses an ammonia-aldehyde condensation reaction to prepare conjugated microporous polymer-coated monodisperse nano-solid silica microspheres. Since the molecular skeleton in the conjugated microporous polymer is a rigid conjugated planar structure, it has good fluorescence properties. When its surface chemical sites are in contact with Fe 3+ or Cr 3+ After the reaction, the conjugated microporous polymer will produce fluorescence quenching phenomenon, and the degree of fluorescence quenching will be related to Fe 3+ or Cr 3+ Therefore, monodisperse composite nano-silica microspheres can be used for qualitative and quantitative fluorescence detection of Fe in aqueous solution. 3+ and Cr 3+ . Summary of the invention
[0005] The purpose of the present invention is to provide a conjugated microporous polymer-coated monodisperse nano-solid silica microsphere material and its preparation and application, specifically, the conjugated microporous polymer-coated monodisperse nano-solid silica microsphere can be used for qualitative and quantitative fluorescence detection of Fe in aqueous solution 3+ and Cr 3+ .
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] (1) Preparation of amino-functionalized monodisperse nano-solid silica microspheres
[0008] In a container, 1-10 mL of deionized water, 5-40 mL of ammonia water with a mass concentration range of 10-30%, and 50-150 mL of anhydrous ethanol are added in sequence; the solution is mixed evenly by mechanical stirring at a speed of 150-400 r / min for 10-20 min; a mixed solution consisting of 0.5-5 mL of ethyl orthosilicate and 20-100 mL of anhydrous ethanol is added dropwise at 20-60° C.; after the addition is completed, the reaction is continued for 2-8 hours; solid-liquid separation is performed to obtain monodisperse nano solid silica microspheres, the monodisperse nano solid silica microspheres are washed with ethanol for 3-6 times, and dried in a vacuum drying oven at 40-80° C. for 8-24 hours;
[0009] Weigh 2.0-6.0g of monodisperse nano solid silica microspheres in a container, add 25-75mL of anhydrous toluene; after dispersion and mixing, introduce nitrogen for 10-20min, add 0.5-7.5mL of 3-aminopropyltriethoxysilane under mechanical stirring at a speed of 100-400r / min, raise the temperature to 80-120°C, and heat under reflux for 16-32h; the obtained solid product is washed with toluene and ethanol for 3-6 times respectively, and placed in a vacuum drying oven at 40-80°C for 8-24h to obtain amino-functionalized monodisperse nano solid silica microspheres.
[0010] (2) Preparation of monodisperse nano-solid silica microspheres coated with conjugated microporous polymers
[0011] First, 0.1-1.0 g of amino-functionalized monodisperse nano-solid silica microspheres are weighed into a container, and 10-30 mL of a mixed solution of 1,4-dioxane and N,N-dimethylformamide (the volume content of 1,4-dioxane in the mixed solution is 5-50%) is added, and the mixture is dispersed and mixed; then, under nitrogen protection, 0.015-0.055 g of one or more of isophthalaldehyde, terephthalaldehyde, and 4,4'-biphenyldicarboxaldehyde, and 0.015-0.055 g of the mixture are added into the flask in sequence. 1,5,9-Triaminotriphenylene and 0.005-0.150 mL of a 2-6 mol / L aqueous hydrochloric acid solution are refluxed at 50-100 ° C with a mechanical stirring speed of 100-400 r / min for 16-48 h; the obtained solid product is washed with 1,4-dioxane and tetrahydrofuran for 3-6 times respectively; finally, it is placed in a vacuum drying oven at 40-80 ° C and dried for 8-24 h to obtain conjugated microporous polymer-coated monodisperse nano-solid silica microspheres, recorded as CMP@SiO2.
[0012] The present invention relates to a monodisperse nano-solid silica microsphere material (silica nanospheres, SiO2) coated with a conjugated microporous polymer (conjugated microporous polymer, CMP), and its preparation and application. The "one-pot method" strategy is mainly adopted, with amino-functionalized monodisperse nano-solid silica microspheres as the matrix, isophthalaldehyde / terephthalaldehyde / 4,4'-biphenyldicarboxaldehyde and 1,5,9-triaminotriphenylene as the functional monomers of the coating layer, and an ammonia-aldehyde condensation reaction is carried out under the action of acid catalysis to coat the surface of the monodisperse nano-solid silica microsphere with a layer of conjugated microporous polymer to form monodisperse composite nano-solid silica microspheres. Since the molecular skeleton in the conjugated microporous polymer is a rigid conjugated planar structure, it has good fluorescence properties. When its surface chemical reaction site is combined with Fe 3+ or Cr 3+ After the reaction, the conjugated microporous polymer will produce fluorescence quenching phenomenon, and the degree of fluorescence quenching is related to Fe 3+ or Cr 3+ Therefore, monodisperse composite nano-solid silica microspheres can be used for qualitative and quantitative fluorescence detection of Fe in aqueous solution. 3+ or Cr 3+ .
[0013] The present invention has the following advantages:
[0014] 1. The material preparation process is simple, the raw materials are easily available, and it can be produced in large quantities.
[0015] 2. The material is a composite structure, with nano-silica microspheres as the matrix, which improves the monodispersity. The coated conjugated microporous polymer molecular skeleton presents a rigid conjugated planar structure and has open pores, which produces more chemical action sites and allows more substances to be detected to interact with it, so it has good fluorescence detection performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of preparing m-CMP@SiO2 material in Example 1.
[0017] Figure 2 Helium ion electron microscopy images of monodisperse nano-solid silica microspheres and CMP@SiO2 microspheres prepared in the examples: (a) monodisperse nano-solid silica microspheres; (b) m-CMP@SiO2; (c) p-CMP@SiO2; (d) bi-CMP@SiO2; (e) o-CMP@SiO2.
[0018] Figure 3 Nitrogen adsorption-desorption curves and pore size distribution of monodisperse nano-solid silica microspheres and x-CMP@SiO2 (x = o-o, m-m, p-p, bi-bi) prepared in the embodiment.
[0019] Figure 4 Infrared spectra of monodisperse nano-solid silica microspheres and x-CMP@SiO2 (x = o-o, m-m, p-p, bi-bi) prepared in the examples.
[0020] Figure 5 This is a qualitative fluorescence detection diagram of metal ions by m-CMP@SiO2 microspheres prepared in Example 1.
[0021] Figure 6 The m-CMP@SiO2 material prepared in Example 1 has a 3+ and Cr 3+ Fluorescence quantitative detection diagram.
[0022] Figure 7 This is a qualitative fluorescence detection diagram of metal ions of the p-CMP@SiO2 material prepared in Example 2.
[0023] Figure 8 The p-CMP@SiO2 material prepared in Example 2 has a 3+ and Cr 3+ Fluorescence quantitative detection diagram.
[0024] Fig. 9 This is the qualitative fluorescence detection diagram of metal ions of the bi-CMP@SiO2 material prepared in Example 3.
[0025] Fig.10The bi-CMP@SiO2 material prepared in Example 3 has a 3+ and Cr 3+ Fluorescence quantitative detection diagram.
[0026] Fig.11 This is the fluorescence detection image of the o-CMP@SiO2 material prepared in comparative example. DETAILED DESCRIPTION
[0027] Example 1: Preparation of monodisperse nano-solid silica microspheres coated with conjugated microporous polymer (m-CMP@SiO2) and its application in qualitative and quantitative fluorescence detection of Fe in aqueous solution 3+ and Cr 3+ application.
[0028] The preparation process of monodisperse nano-solid silica microspheres coated with conjugated microporous polymer is as follows: Figure 1 shown.
[0029] (1) Preparation of amino-functionalized monodisperse nano-solid silica microspheres
[0030] In a three-necked flask, 6.5 mL of deionized water, 19 mL of ammonia water with a mass concentration of 28%, and 134 mL of anhydrous ethanol were added in sequence; the solution was mixed evenly by mechanical stirring at a speed of 300 r / min for 10 min; a mixed solution consisting of 1 mL of ethyl orthosilicate and 55 mL of anhydrous ethanol was added dropwise at 30°C; after the addition was completed, the reaction was continued for 5 h; solid-liquid separation was performed to obtain monodisperse nano-solid silica microspheres, and the monodisperse nano-solid silica microspheres were washed with ethanol for 4 times, and dried in a vacuum drying oven at 60°C for 12 h;
[0031] Weigh 3.0 g of monodisperse nano-solid silica microspheres into a three-necked flask, add 60 mL of anhydrous toluene; after dispersion and mixing, introduce nitrogen for 15 minutes, add 3 mL of 3-aminopropyltriethoxysilane under mechanical stirring at a speed of 200 r / min, raise the temperature to 90°C, and heat to reflux for 24 hours; the obtained solid product is washed with toluene and ethanol four times respectively, and placed in a vacuum drying oven at 60°C for 12 hours to obtain amino-functionalized monodisperse nano-solid silica microspheres.
[0032] (2) Preparation of monodisperse nano-solid silica microspheres coated with conjugated microporous polymers
[0033] First, 0.3 g of amino-functionalized monodisperse nano-solid silica microspheres were weighed into a container, and 20 mL of a mixed solution of 1,4-dioxane and N,N-dimethylformamide (the volume content of 1,4-dioxane in the mixed solution was 10%) was added and dispersed and mixed evenly; then, under nitrogen protection, 0.022 g of isophthalaldehyde, 0.030 g of 1,5,9-triaminotriphenylene and 0.020 mL of a 3 mol / L aqueous hydrochloric acid solution were added to the flask in sequence, and refluxed for 24 h at 80 ° C with a mechanical stirring speed of 200 r / min; the obtained solid product was washed with 1,4-dioxane and tetrahydrofuran 4 times each in sequence; finally, it was placed in a vacuum drying oven at 60 ° C and dried for 12 h to obtain monodisperse nano-solid silica microspheres coated with conjugated microporous polymers, recorded as m-CMP@SiO2.
[0034] (3) Qualitative fluorescence detection of metal ions by m-CMP@SiO2 material:
[0035] Deionized water was used to prepare m-CMP@SiO2 5mg / L suspension and the samples containing different metal ions (Li + Na + K + Ca 2+ Cd 2+ Co 2+ Cu 2+ Hg 2+ Mg 2+ Mn 2+ Ni 2+ Zn 2+ Pb 2+ Fe 3+ Al 3+ or Cr 3+ , the anions are all Cl - ) aqueous solution (10mmol / L). The suspension containing m-CMP@SiO2 was mixed with the aqueous solution of metal ions to be detected in proportion and then subjected to fluorescence detection. During the detection, the concentration of m-CMP@SiO2 in the system was 0.25mg / mL, and the concentration of metal ions was 200μmol / L. A blank control group without metal ions was set (the concentration of m-CMP@SiO2 in the system was 0.25mg / mL). The fluorescence spectrophotometer was uniformly set to an excitation wavelength of 469nm and an emission wavelength of 567nm.
[0036] (4) Effect of m-CMP@SiO2 on Fe 3+ With Cr 3+ To perform quantitative fluorescence detection:
[0037] A series of different concentrations of Fe 3+ With Cr3+ solution (0, 20, 40, 60, 80, 100, 150, 200, 250, 300, 400 μmol / L), the suspension containing m-CMP@SiO2 was mixed with the metal ion Fe 3+ or Cr 3+ Aqueous solution (where the anions are all Cl - ) were mixed and then subjected to fluorescence detection. During the detection, the concentration of m-CMP@SiO2 material in the system was kept at 0.25 mg / mL, and a blank control group without metal ions was set (the concentration of m-CMP@SiO2 in the system was 0.25 mg / mL). The fluorescence spectrophotometer was uniformly set to an excitation wavelength of 469 nm and an emission wavelength of 567 nm.
[0038] Product characterization
[0039] The monodisperse nano-solid silica microspheres coated with conjugated microporous polymer prepared in Example 1 are as follows Figure 2 As shown, (a) amino-functionalized monodisperse nano-solid silica microspheres, with an average particle size of 200nm, (b) m-CMP@SiO2, with an average particle size of 220nm. It was found that the surface of the amino-functionalized monodisperse nano-solid silica microspheres without shell coating was very smooth and had good monodispersity. When the amino-functionalized monodisperse nano-solid silica microspheres were coated with conjugated microporous polymer shells, their surfaces became rough. After the materials were coated with conjugated microporous polymers, the average particle size increased by 20nm, proving that the conjugated microporous polymers were successfully coated on the surface of the amino-functionalized monodisperse nano-solid silica microspheres, and the thickness of the conjugated microporous polymer shells ranged from 10 to 30nm.
[0040] Figure 3 (a, b) show the nitrogen adsorption-desorption curves and pore size distribution of amino-functionalized monodisperse nano-solid silica microspheres and m-CMP@SiO2. It is found that the specific surface area of amino-functionalized monodisperse nano-solid silica microspheres is 3.53 m 2 / g, the surface is solid and has no pores. The specific surface area of m-CMP@SiO2 is 26.1m 2 / g, the pore size distribution is between 2.0 and 15 nm. The specific surface area and pore size of the material change significantly before and after coating with the conjugated microporous polymer, which proves that the conjugated microporous polymer is successfully coated on the surface of amino-functionalized monodisperse nano-solid silica microspheres.
[0041] Figure 4 The infrared spectra of amino-functionalized monodisperse nano-solid silica microspheres and m-CMP@SiO2 are shown in Figure 1. From the figure, it can be found that 1054 and 795 cm-1 appear in both spectra. -1The strong absorption peaks are attributed to the asymmetric stretching vibration absorption peak and the symmetric stretching vibration absorption peak of the Si-O-Si bond. -1 The absorption peak is attributed to the imine bond in the shell of the conjugated microporous polymer, proving that isophthalaldehyde and 1,5,9-triaminotriphenylene undergo an ammonia aldehyde condensation reaction, which further proves that the conjugated microporous polymer is successfully coated on the surface of amino-functionalized monodisperse nano-solid silica microspheres.
[0042] Product Application
[0043] Figure 5 The results of qualitative fluorescence detection of m-CMP@SiO2 materials for different metal ions. It can be found from the figure that when the m-CMP@SiO2 material without metal ions is tested for fluorescence, it has a very strong fluorescence response signal. + Na + K + Ca 2+ Cd 2+ Co 2+ Cu 2+ Hg 2+ Mg 2+ Mn 2+ Ni 2+ Zn 2+ Pb 2+ or Al 3+ There was no significant change in the fluorescence signal after adding Fe 3 + or Cr 3+ After that, the fluorescence intensity of the m-CMP@SiO2 material decreased to a certain extent, which was manifested as fluorescence quenching.
[0044] Figure 6 The m-CMP@SiO2 material has a 3+ or Cr 3+ The quantitative fluorescence detection results show that m-CMP@SiO2 material has a strong 3+ The fluorescence intensity increases with the concentration of Fe in the range of 0 to 400 μM. 3+ The linear correlation coefficient is R=0.989. 3+ The fluorescence intensity increases with the concentration of Cr in the range of 0 to 400 μM. 3+ The linear correlation coefficient was R=0.984.
[0045] Example 2: Preparation of monodisperse nano-solid silica microspheres coated with conjugated microporous polymer (p-CMP@SiO2) and its application in qualitative and quantitative fluorescence detection of Fe in aqueous solution 3+ and Cr 3+application.
[0046] (1) The preparation process of conjugated microporous polymer-coated silica microspheres p-CMP@SiO2 material is the same as that in Example 1, except that the functional monomer isophthalaldehyde is replaced by terephthalaldehyde, and other preparation conditions remain unchanged.
[0047] (2) The qualitative and quantitative detection process of metal ions by p-CMP@SiO2 material is the same as that in Example 1.
[0048] Product characterization
[0049] The p-CMP@SiO2 material prepared in Example 2 has the following morphology: Figure 2 As shown in (c), when the amino-functionalized monodisperse nano-solid silica microspheres are coated with a conjugated microporous polymer shell, their surface becomes rough. The average particle size of p-CMP@SiO2 is 230 nm. After the material is coated with the conjugated microporous polymer, the average particle size increases by 30 nm, proving that the conjugated microporous polymer is coated on the surface of the amino-functionalized monodisperse nano-solid silica microspheres, and the thickness of the conjugated microporous polymer shell ranges from 20 to 40 nm.
[0050] Figure 3 (c, d) show the nitrogen adsorption-desorption curve and pore size distribution of p-CMP@SiO2. It is found that the specific surface area of p-CMP@SiO2 is 44.6 m 2 / g, the pore size distribution is between 2.4 and 10 nm. The specific surface area and pore size of the material change significantly before and after coating with the conjugated microporous polymer, which proves that the conjugated microporous polymer is successfully coated on the surface of amino-functionalized monodisperse nano-solid silica microspheres.
[0051] Figure 4 The infrared spectrum of p-CMP@SiO2 material is shown in the figure. 1624 cm -1 The absorption peak is attributed to the imine bond in the shell of the conjugated microporous polymer, proving that terephthalaldehyde and 1,5,9-triaminotriphenylene undergo an ammonia aldehyde condensation reaction, which further proves that the conjugated microporous polymer is successfully coated on the surface of amino-functionalized monodisperse nano-solid silica microspheres.
[0052] Product Application
[0053] Figure 7 The results of qualitative fluorescence detection of p-CMP@SiO2 materials for different metal ions are shown in the figure. It can be found that when the p-CMP@SiO2 material without metal ions is tested for fluorescence, it has a very strong fluorescence response signal. + Na + K + Ca 2+Cd 2+ Co 2+ Cu 2+ Hg 2+ Mg 2+ Mn 2+ Ni 2+ Zn 2+ Pb 2+ Al 3+ There was no significant change in the fluorescence signal after adding Fe 3+ or Cr 3+ After that, the fluorescence intensity of the p-CMP@SiO2 material decreased to a certain extent, which was manifested as fluorescence quenching.
[0054] Figure 8 The p-CMP@SiO2 material has a 3+ or Cr 3+ The quantitative fluorescence detection results show that p-CMP@SiO2 material has a strong affinity for Fe 3+ The fluorescence intensity increases with the concentration of Fe in the range of 0 to 200 μM. 3+ The linear correlation coefficient is R=0.993. 3+ The fluorescence intensity increases with the concentration of Cr in the range of 0 to 300 μM. 3+ The linear correlation coefficient was R=0.984.
[0055] Example 3: Preparation of monodisperse nano-solid silica microspheres coated with conjugated microporous polymer (bi-CMP@SiO2) and its application in qualitative and quantitative fluorescence detection of Fe in aqueous solution 3+ and Cr 3+ application.
[0056] (1) The preparation process of conjugated microporous polymer-coated silica microspheres bi-CMP@SiO2 material is the same as that in Example 1, except that the functional monomer isophthalaldehyde is replaced by 4,4'-biphenyldicarboxaldehyde, and other preparation conditions remain unchanged.
[0057] (2) The qualitative and quantitative detection process of metal ions by bi-CMP@SiO2 material is the same as that in Example 1.
[0058] Product characterization
[0059] The morphology of the bi-CMP@SiO2 material prepared in Example 3 is as follows Figure 2As shown in (d), when the amino-functionalized monodisperse nano-solid silica microspheres are coated with a conjugated microporous polymer shell, their surface becomes rough. The average particle size of bi-CMP@SiO2 is 225 nm. After the material is coated with the conjugated microporous polymer, the average particle size increases by 25 nm, proving that the conjugated microporous polymer is coated on the surface of the amino-functionalized monodisperse nano-solid silica microspheres, and the thickness of the conjugated microporous polymer shell is 20 to 30 nm.
[0060] Figure 3 (e, f) shows the nitrogen adsorption-desorption curve and pore size distribution of bi-CMP@SiO2. It is found that the specific surface area of bi-CMP@SiO2 is 30.9 m 2 / g, the pore size is mainly distributed between 1.8 and 10 nm. The specific surface area and pore size of the material change significantly before and after coating with the conjugated microporous polymer, which proves that the conjugated microporous polymer is successfully coated on the surface of amino-functionalized monodisperse nano-solid silica microspheres.
[0061] Figure 4 The infrared spectrum of bi-CMP@SiO2 material is shown in the figure. 1624 cm -1 The absorption peak is attributed to the imine bond in the shell of the conjugated microporous polymer, indicating that 4,4'-biphenyldicarboxaldehyde and 1,5,9-triaminotriphenylene undergo an ammonia aldehyde condensation reaction, further proving that the conjugated microporous polymer is successfully coated on the surface of amino-functionalized monodisperse nano-solid silica microspheres.
[0062] Product Application
[0063] Fig. 9 The results of qualitative fluorescence detection of bi-CMP@SiO2 materials for different metal ions. It can be seen from the figure that when the bi-CMP@SiO2 material without metal ions is tested for fluorescence, it has a very strong fluorescence response signal. + Na + K + Ca 2+ Cd 2+ Co 2+ Cu 2+ Hg 2+ Mg 2+ Mn 2+ Ni 2+ Zn 2+ Pb 2+ Al 3+ There was no significant change in the fluorescence signal after adding Fe 3+ or Cr 3+ After that, the fluorescence intensity of the bi-CMP@SiO2 material decreased to a certain extent, which was manifested as fluorescence quenching.
[0064] Fig.10 The bi-CMP@SiO2 material has good 3+ or Cr 3+ The quantitative fluorescence detection results show that bi-CMP@SiO2 material has a strong affinity for Fe 3+ The fluorescence intensity increases with the concentration of Fe in the range of 0 to 200 μM. 3+ The linear correlation coefficient is R=0.988. 3+ The fluorescence intensity increases with the concentration of Cr in the range of 0 to 400 μM. 3+ The linear correlation coefficient was R=0.989.
[0065] Comparative Example: Preparation of monodisperse nano-solid silica microspheres coated with conjugated microporous polymer (o-CMP@SiO2) and its application in qualitative and quantitative fluorescence detection of Fe in aqueous solution 3+ and Cr 3+ application.
[0066] (1) The preparation process of o-CMP@SiO2 material coated with conjugated microporous polymer is the same as that in Example 1, except that the functional monomer isophthalaldehyde is replaced by o-phthalaldehyde, and other preparation conditions remain unchanged.
[0067] (2) The qualitative and quantitative detection process of metal ions by o-CMP@SiO2 material is the same as that in Example 1.
[0068] Product characterization
[0069] The morphology of o-CMP@SiO2 material prepared in the comparative example is as follows Figure 2 As shown in (e), when the amino-functionalized monodisperse nano-solid silica microspheres are coated with a conjugated microporous polymer shell, their surface does not change significantly. The average particle size of o-CMP@SiO2 is 203 nm. The average particle size increases by 3 nm after the material is coated with the conjugated microporous polymer. The thickness of the conjugated microporous polymer shell is 0 to 6 nm.
[0070] Figure 3 (c, d) show the nitrogen adsorption-desorption curve and pore size distribution of o-CMP@SiO2. It is found that the specific surface area of o-CMP@SiO2 is 4.15 m 2 / g, and the surface has no porous structure, which can be considered that the steric hindrance of o-phthalaldehyde is too large and fails to undergo cross-linking reaction with the amino-containing monomer.
[0071] Figure 4 The infrared spectrum of o-CMP@SiO2 material is shown in the figure. 1690cm -1The absorption peak is attributed to the C=O bond in the functional monomer o-phthalaldehyde, indicating that the ammonia-aldehyde condensation reaction is not complete.
[0072] Comprehensive morphology, specific surface area, pore size and infrared characterization results before and after material coating show that the conjugated microporous polymer was not coated on the surface of amino-functionalized monodisperse nano-solid silica microspheres, and o-CMP@SiO2 was not successfully prepared.
[0073] Product Application
[0074] The fluorescence spectrum of o-CMP@SiO2 material is shown in Fig. 9 As shown, the material does not generate any fluorescence signal, which proves that the material has no fluorescence properties, so subsequent qualitative and quantitative fluorescence detection of metal ions cannot be carried out.
[0075] Based on the application results of Examples 1, 2, 3 and the comparative materials, it was found that when other preparation conditions remained unchanged, by changing the aldehyde functional monomers in the ammonia-aldehyde condensation reaction: o-phthalaldehyde / isophthalaldehyde / terephthalaldehyde / 4,4'-biphenyldicarboxaldehyde, the fluorescence properties of the prepared conjugated microporous polymer-coated monodisperse nano-solid silica microsphere materials had obvious differences, among which the m-CMP@SiO2 material prepared by the isophthalaldehyde functional monomer had a significant difference in the fluorescence properties of Fe 3+ and Cr 3+ It has a wider detection range and more sensitive detection ability. The o-CMP@SiO2 material prepared by o-phthalaldehyde functional monomer has no fluorescence performance. At the same time, p-CMP@SiO2 and bi-CMP@SiO2 materials were successfully prepared using terephthalaldehyde / 4,4'-biphenyldicarboxaldehyde functional monomers and used for Fe 3+ and Cr 3+ Fluorescence qualitative and quantitative detection.
[0076] The monodisperse nano-solid silica microsphere material coated with conjugated microporous polymer is a composite structure, with nano-silica microspheres as the matrix, which improves the monodispersity of the material. The coated conjugated microporous polymer molecular skeleton presents a rigid conjugated planar structure and has open pores, thereby generating more chemical action sites, allowing more substances to be detected to interact with it, so it has good fluorescence detection capabilities. The raw materials of the material are easy to obtain, the preparation process is simple, and it can be mass-produced.
Claims
1. A method for preparing monodisperse nano-solid silica microspheres coated with a conjugated microporous polymer, characterized in that: The monodisperse nano solid silica microspheres functionalized with amino groups, aldehyde and 1,5,9-triaminotriphenylene are used as raw materials. Under the action of acid catalysis, an ammonia-aldehyde condensation reaction is used to coat a layer of conjugated microporous polymer on the surface of the monodisperse nano solid silica microspheres. The aldehyde is one or more of isophthalaldehyde, terephthalaldehyde and 4,4'-biphenyldicarboxaldehyde.
2. The preparation method according to claim 1, characterized in that: Monodisperse nano-solid silica microspheres functionalized with amino groups were used as raw materials; One or more of isophthalaldehyde, terephthalaldehyde, 4,4'-biphenyldicarboxaldehyde and 1,5,9-triaminotriphenylene are used as functional monomers of the coating layer, and an ammonia-aldehyde condensation reaction is carried out under acid catalysis to form a conjugated microporous polymer shell layer; The acid catalyst is aqueous hydrochloric acid; The solvents used were 1,4-dioxane and N,N-dimethylformamide.
3. The preparation method according to claim 1 or 2, characterized in that: The preparation process of amino-functionalized monodisperse nano-solid silica microspheres can be carried out according to the following steps: In a container, 1-10 mL of deionized water, 5-40 mL of ammonia water with a mass concentration range of 10-30%, and 50-150 mL of anhydrous ethanol are added in sequence; the solution is mixed evenly by mechanical stirring at a speed of 150-400 r / min for 10-20 min; a mixed solution consisting of 0.5-5 mL of ethyl orthosilicate and 20-100 mL of anhydrous ethanol is added dropwise at 20-60 °C; after the addition is completed, the reaction is continued for 2-8 h; solid-liquid separation is performed to obtain monodisperse nano-solid silica microspheres, the monodisperse nano-solid silica microspheres are washed with ethanol for 3-6 times, and dried in a vacuum drying oven at 40-80 °C for 8-24 h; 2.0-6.0 g of monodisperse nano solid silica microspheres are weighed into a container, and 25-75 mL of anhydrous toluene is added; after dispersion and mixing, nitrogen is introduced for 10-20 min, and 0.5-7.5 mL of 3-aminopropyltriethoxysilane is added under mechanical stirring at a speed of 100-400 r / min, the temperature is raised to 80-120 ° C, and heated to reflux for 16-32 h; the obtained solid product is washed with toluene and ethanol for 3-6 times respectively, and placed in a vacuum drying oven at 40-80 ° C for 8-24 h to obtain amino-functionalized monodisperse nano solid silica microspheres.
4. The preparation method according to claim 1, characterized in that: The preparation process of monodisperse nano-solid silica microspheres coated with conjugated microporous polymer can be carried out according to the following steps: First, 0.1-1.0 g of amino-functionalized monodisperse nano-solid silica microspheres are weighed into a container, and 10-30 mL of a mixed solution of 1,4-dioxane and N,N-dimethylformamide is added, wherein the volume content of 1,4-dioxane in the mixed solution is 5-50%, and the mixture is dispersed and mixed. Then, under nitrogen protection, 0.015-0.055 g of one or more of isophthalaldehyde, terephthalaldehyde, and 4,4'-biphenyldicarboxaldehyde, 0.015-0.055 g of 1,5,9-triaminotriphenylene and 0.005-0.150 mL of a 2-6 mol / L hydrochloric acid aqueous solution are added to the flask in sequence, and the mixture is refluxed for 16-48 ℃ at a mechanical stirring speed of 100-400 r / min. h; the obtained solid product was washed with 1,4-dioxane and tetrahydrofuran for 3 to 6 times respectively; finally, it was dried in a vacuum drying oven at 40 to 80 °C for 8 to 24 h to obtain monodisperse nano-solid silica microspheres coated with conjugated microporous polymers, which were recorded as CMP@SiO2.
5. The preparation method according to claim 4, characterized in that: The preparation process of monodisperse nano-solid silica microspheres coated with conjugated microporous polymer can be carried out according to the following steps: First, 0.1-1.0 g of amino-functionalized monodisperse nano-solid silica microspheres are weighed into a container, and 10-30 mL of a mixed solution of 1,4-dioxane and N,N-dimethylformamide is added, wherein the volume content of 1,4-dioxane in the mixed solution is 5-50%, and the mixture is dispersed and mixed evenly; then, under nitrogen protection, 0.015-0.035 g of one or more of isophthalaldehyde, terephthalaldehyde, and 4,4'-biphenyldicarboxaldehyde, 0.025-0.045 g of 1,5,9-triaminotriphenylene and 0.005-0.150 mL of a 2-6 mol / L hydrochloric acid aqueous solution are added to the flask in sequence, and the mixture is refluxed for 16-48 ℃ at a mechanical stirring speed of 100-400 r / min under the condition of 50-100 ℃. h; the obtained solid product was washed with 1,4-dioxane and tetrahydrofuran for 3 to 6 times respectively; finally, it was dried in a vacuum drying oven at 40 to 80 °C for 8 to 24 h to obtain monodisperse nano-solid silica microspheres coated with conjugated microporous polymers, which were recorded as CMP@SiO2.
6. Monodisperse nano-solid silica microspheres coated with a conjugated microporous polymer prepared by the preparation method according to any one of claims 1 to 5.
7. The microsphere according to claim 6, characterized in that: The amino-functionalized monodisperse nano-silica microspheres have a particle size range of 150-350 nm, a thickness range of 10-50 nm of the conjugated microporous polymer coating layer, and a specific surface area range of 1-50 m 2 g -1 The pore size of the micropores ranges from 0.5 to 25 nm.
8. The microsphere according to claim 6, characterized in that: The amino-functionalized monodisperse nano-silica microspheres have a particle size range of 180-220 nm, a thickness range of 15-25 nm for the conjugated microporous polymer coating layer, and a specific surface area range of 1-50 m 2 g -1 The pore size of the micropores ranges from 0.5 to 25 nm.
9. An application of monodisperse nano solid silica microspheres coated with a conjugated microporous polymer according to any one of claims 6 to 8, characterized in that: The microsphere material is used for qualitative or quantitative fluorescence detection of Fe in aqueous solution. 3+ or Cr 3+ .
Citation Information
Patent Citations
Preparation method of fluorescent silica microspheres for rapidly and quantitatively detecting iron ions
CN107952403A
Microporous polymer coated hydrophilic resin and application thereof in glycopeptide enrichment
CN110152624A